2022
DOI: 10.1007/s10758-022-09602-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers’ Reflections on Attitudes Towards Teaching and Learning Mathematics with Online Platforms at School: A Case Study in the Context of a University Online Training

Abstract: Online learning platforms take over a new role in education, especially in times of the Covid-19 pandemic. This paper will discuss pre-service teachers’ reflections on attitudes towards online learning platforms and the respective changes due to an online training of using this digital tool in mathematics classes. The special training took place in a bachelor seminar with fourteen participants on the use of digital media in mathematics education at the University of Siegen. Based on the ‘Tripartite Model of At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…As in our study, the opportunities offered by the technologies to provide continuity of education during the quarantine were also recognized by Mulenga and Marbán ( 2020b ), who considered COVID-19 as a gateway for digital learning in mathematics education, and by Alabdulaziz ( 2021 ), who observed that teachers positively valued technology as a means to overcome difficulties and promote mathematics learning in distance education. As in the studies conducted by Nketsia, et al ( 2021 ), Dilling and Vogler ( 2022 ), and Naidoo ( 2020 ), the PMTs participating in our study used digital platforms to receive their classes. We agree with these authors when they argue that the use of technologies favored the generation of positive perceptions for the PTs regarding their usefulness in RE and emphasize the need to build their confidence in the use of technologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in our study, the opportunities offered by the technologies to provide continuity of education during the quarantine were also recognized by Mulenga and Marbán ( 2020b ), who considered COVID-19 as a gateway for digital learning in mathematics education, and by Alabdulaziz ( 2021 ), who observed that teachers positively valued technology as a means to overcome difficulties and promote mathematics learning in distance education. As in the studies conducted by Nketsia, et al ( 2021 ), Dilling and Vogler ( 2022 ), and Naidoo ( 2020 ), the PMTs participating in our study used digital platforms to receive their classes. We agree with these authors when they argue that the use of technologies favored the generation of positive perceptions for the PTs regarding their usefulness in RE and emphasize the need to build their confidence in the use of technologies.…”
Section: Discussionmentioning
confidence: 99%
“…We identified studies regarding two topics. On one hand, researchers have been preoccupied with understanding visions, perceptions, attitudes, learning, and factors that have an impact on the use of technologies, on behalf of PTs during the transition from face-to-face classes to RE mode (Dilling & Vogler, 2022 ; Long et al, 2022 ; Mulenga & Marbán, 2020a , 2020b ; Naidoo, 2020 ; Nketsia et al, 2021 ). On the other hand, the researchers have documented actions taken in order to reorganize curriculum and give continuity to important processes in the PTs’ education, such as teaching practices in schools (Adams et al, 2021 ; Kim, 2020 ; Rodrigues & Garcia, 2022 ).…”
Section: Preservice Teacher (Pt) Education and Technologies During Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…Attitudes towards to distance education can be conceptually defined as a psychological tendency expressed by evaluating the online learning environment with some degree of satisfied or dissatisfied (Demirel, 2022;Kaban, 2021;Tzivinikou et al, 2021). Because of its strong relationship with behaviors, attitudes are seen as one of the main factors in students' orientation to a course or subject in both face-to-face and online learning environments (Dilling & Vogler, 2022;Petscher, 2010).…”
Section: Attitudes Towards Distance Education and Academic Satisfactionmentioning
confidence: 99%